Construction of the Sai Education Centre at Plot 68 Uniaville, South of Johannesburg - Govindasamy, N. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2007.